Pengembangan Modul Pembelajaran Mobile Berbasis Microlearning dalam Flipbook pada Materi Sistem Persamaan Linear Dua Variabel di Kelas X di SMAN 1 Sorkam - Nazla Elpina; Denny Haris (Journal on Education, 2023)
This research has the aim of developing and producing a mobile learning module product based on microlearning that is valid, practical and effective for use on the material of a two-variable linear equation system. The type of research used is research and development (Research and Development) which refers to the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The subjects used in this study were students of class X SMA N 1 Sorkam, totaling 35 people. Besides, the object of this research is a mobile learning module based on microlearning.